2014
DOI: 10.1038/ki.2014.218
|View full text |Cite
|
Sign up to set email alerts
|

The urea decomposition product cyanate promotes endothelial dysfunction

Abstract: The dramatic cardiovascular mortality of chronic kidney disease patients is attributable in a significant proportion to endothelial dysfunction. Cyanate, a reactive species in equilibrium with urea, is formed in excess in chronic kidney disease. Cyanate is thought to have a causal role in promoting cardiovascular disease, but the underlying mechanisms remain unclear. Immunohistochemical analysis performed in the present study revealed that carbamylated epitopes associate mainly with endothelial cells in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 35 publications
0
46
1
4
Order By: Relevance
“…The involvement of carbamylated proteins in mortality (53) and degenerative complications linked to CKD, such as atherosclerosis and insulin resistance (18,54), has been highlighted in several studies. We found that cyanate levels, within the range present in CKD mice and humans (18,37), attenuate insulin secretion in normal mouse islets ex vivo and that this was prevented by the antioxidant NAC. However, in contrast to the effects of urea, cyanate did not increase protein O-GlcNAcylation, and DON did not restore insulin secretion in the presence of cyanate.…”
Section: Increased Protein O-glcnacylation Alters Glucose Metabolism mentioning
confidence: 88%
See 1 more Smart Citation
“…The involvement of carbamylated proteins in mortality (53) and degenerative complications linked to CKD, such as atherosclerosis and insulin resistance (18,54), has been highlighted in several studies. We found that cyanate levels, within the range present in CKD mice and humans (18,37), attenuate insulin secretion in normal mouse islets ex vivo and that this was prevented by the antioxidant NAC. However, in contrast to the effects of urea, cyanate did not increase protein O-GlcNAcylation, and DON did not restore insulin secretion in the presence of cyanate.…”
Section: Increased Protein O-glcnacylation Alters Glucose Metabolism mentioning
confidence: 88%
“…Taken together, these data indicate that urea impairs GSIS by increasing ROS and protein O-GlcNAcylation in both rodent and human islets. Urea is in equilibrium with the electrophilic species cyanate, which can alter protein function by reacting with the amino group of lysine residues, resulting in the generation of ε-aminocarbomyl-lysine (37). Under physiological conditions, 0.8% of the molar concentration of urea is converted to cyanate.…”
Section: Urea Impairs Insulin Secretion By Increasing Ros Production mentioning
confidence: 99%
“…We further showed that carbamylated proteins were themselves pro-inflammatory and triggered T cell activation (44). Moreover, recent studies by others have shown that either direct OCN Ϫ exposure to endothelial cells in culture, or via infusion in vivo, promotes protein carbamylation, is pro-inflammatory and inhibits NO-dependent functions (45,46). Airway lining fluid has high levels (millimolar) of SCN Ϫ , where it exerts bacteriostatic activity (47 (28), we first tested whether isolated human EPO could catalyze protein carbamylation, as monitored by proteinbound HCit, under physiological conditions of enzyme and reactants.…”
mentioning
confidence: 89%
“…Protein carbamylation generated by peroxidase-catalyzed oxidation of thiocyanate also predicts CV risk in nonuremic individuals (129,133). Exposure of human coronary artery endothelial cells to cyanate promotes protein carbamylation to levels observed in uremic patients, reduces expression of endothelial nitric oxide synthase, and increases tissue factor and plasminogen activator inhibitor-1 expression in aortic tissue (134). Posttranslational modification by glycation is another mechanism potentially causing dysfunctional HDL in CKD, especially in individuals with CKD and diabetes, by reducing the ability of LCAT to esterify cholesterol and decreasing PON1 levels (101,135140).…”
Section: Introductionmentioning
confidence: 99%